Mental health analysis of cancer-diagnosed patients with the lowest survival rate and their caregivers - Orchi, Irin Hoque; Prarthona, Sabrina Tajrin; Tabassum, Nafisa; Hossain, Jaeemul; Ishti, Iftekhar Alam (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.